A therapeutic chimeric IgG/IgA expressed by CHO cells for oral treatment of PED in piglets - Xiao, Yan; Zhang, Yunjing; Wang, Zhiyan; Zhao, Wenyin; Xu, Xin; Chen, Xiao; Tan, Feifei; Sun, Zhe; Huang, Baicheng; Tian, Kegong (Frontiers in Microbiology, 2022)
Immunoglobulin A (IgA) of sows is critically important for assessing piglets' protective capacity against porcine epidemic diarrhea virus (PEDV). Here, we report a therapeutic chimeric anti-PEDV IgG/IgA expressed by Chinese hamster ovary (CHO) cells for oral treatment of PED. The chimeric anti-PEDV IgG/IgA was produced by the CHO cell lines, in which the heavy chain was constructed by combining the VH, Cγ1 and hinge regions of PEDV IgG mAb 8A3, and the Cα2 and Cα3 domains of a Mus musculus immunoglobulin alpha chain. The chimeric anti-PEDV IgG/IgA could neutralize the strains of CV777 (G1), P014 (G2) and HN1303 (G2) in vitro effectively, showing broad-spectrum neutralization activity. The in vivo challenge experiments demonstrated that chimeric anti-PEDV IgG/IgA (9C4) produced in the CHO cell supernatant could alleviate clinical diarrhea symptoms of the PEDV infection in piglets. In general, our study showed that chimeric anti-PEDV IgG/IgA produced from CHO cell line supernatants effectively alleviates PEDV infection in piglets, which also gives the foundation for the construction of fully functional secretory IgA by the J chain introduction to maximize the antibody therapeutic effect.